Incorporation of Indole Significantly Improves the Transfection Efficiency of Guanidinium-Containing Poly(Methacrylamide)s - Cokca, Ceren; Zartner, Leon; Tabujew, Ilja; Fischer, Dagmar; Peneva, Kalina (Macromolecular Rapid Communications, 2020)
A highly efficient transfection agent is reported that is based on terpolymer consisting of N-(2-hydroxypropyl)methacrylamide (HPMA), N-(3-guanidinopropyl) methacrylamide (GPMA), and N-(2-indolethyl)methacrylamide monomers (IEMA) by analogy to the amphipathic cell-penetrating peptides containing tryptophan and arginine residues. The incorporation of the indole-bearing monomer leads to successful plasmid DNA condensation even at a nitrogen-to-phosphate (N/P) ratio of 1. The hydrodynamic diameter of polyplexes is determined to be below 200 nm for all N/P ratios. The transfection studies demonstrate a 200-fold increase of the transgene expression in comparison to P(HPMA-co-GPMA) with the same guanidinium content. This study reveals the strong potential of the indole group as a side-chain pendant group that can increase the cellular uptake of polymers and the transfection efficiency of the respective polyplexes.
CRIS-Team Scopus Importer:2020-10-13
Keywords: gene delivery; guanidinium; indole; methacrylamide